(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
The literature (mainly by Mwangi 2003 & 2004) on the use of English prepositions in Kenyan English has shown how these were used differently from Standard International English usage. The present study sought to find further evidence for this different usage. It did so by giving a written grammar task to a convenience sample composed of Form Two students of the St. Joseph Nyachenge Secondary School in the Gucha District of Kenya. The task focused on the use of just five prepositions: in, at, on, over and during. It required of the respondents to fill in blank spaces with the appropriate preposition, from a list of prepositions to choose from. The results indicate that three (over, during and in) of the five prepositions were highly misused, at a rate of more than 60%. Although it is not very clear from this study what the main sources of difficulty were for the respondents in choosing the right preposition, the following seem to be good candidates: for some prepositions (like over) it is the different nuances of meaning that seem to have mattered most; for others (like in), the key factors seem to have been the frequency of use of the noun phrase serving as the object of the preposition in question on the one hand and, on the other, the respondents’ own perceived space dimensions of that noun phrase.